2018
DOI: 10.1007/978-3-030-05204-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Robot Knowledge Consultants with Distributed Short Term Memory

Abstract: Human-robot communication in situated environments involves a complex interplay between knowledge representations across a wide variety of modalities. Crucially, linguistic information must be associated with representations of objects, locations, people, and goals, which may be represented in very different ways. In previous work, we developed a Consultant Framework that facilitates modality-agnostic access to information distributed across a set of heterogeneously represented knowledge sources. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For example, Hawes et al (2007) leverage a model of WM within the CoSy architecture, with concessions made to accommodate the realistic needs of integrated robot architectures, in which specialized representations are stored and manipulated within distributed, parallelized, domain-specific components (see also . Similarly, in our own work within the DIARC architecture (Scheutz et al, 2019), we have demonstrated (as we will further discuss in this paper) the use of distributed WM buffers associated with such architectural components (Williams et al, 2018b), as well as hierarchical models of common ground jointly inspired by models of WM (e.g. Cowan, 2001) and models of givenness from natural language pragmatics (e.g.…”
Section: Models Of Working Memory In Integrated Robot Architecturesmentioning
confidence: 70%
See 2 more Smart Citations
“…For example, Hawes et al (2007) leverage a model of WM within the CoSy architecture, with concessions made to accommodate the realistic needs of integrated robot architectures, in which specialized representations are stored and manipulated within distributed, parallelized, domain-specific components (see also . Similarly, in our own work within the DIARC architecture (Scheutz et al, 2019), we have demonstrated (as we will further discuss in this paper) the use of distributed WM buffers associated with such architectural components (Williams et al, 2018b), as well as hierarchical models of common ground jointly inspired by models of WM (e.g. Cowan, 2001) and models of givenness from natural language pragmatics (e.g.…”
Section: Models Of Working Memory In Integrated Robot Architecturesmentioning
confidence: 70%
“…These concerns are addressed by our previously proposed model of robotic short-term memory (Williams et al, 2018b), in which speakers rely on the contents of WM for initial attribute selection and, if their selected referring expression is not fully discriminating, select additional properties using a variant of the IA. While this does not align with dual-process models of cognition, it does account for both encoding and maintenance of WM, and provides a potentially more cognitively plausible account of REG with respect to WM dynamics.…”
Section: Memory-oriented Models Of Referring Expression Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of a consultant is the agent consultant, which stores information about other agents (like humans) with which a robot might interact. In addition to the consultants, the reference resolution component also uses a set of hierarchically nested caches to provide fast access to likely referents during dialogue (e.g., objects that were recently referenced) [58].…”
Section: Architectural Integrationmentioning
confidence: 99%